Experimental Analysis of Mechanical Properties and Durability of Cement-Based Composite with Carbon Nanotube. (1st September 2021) - Du, Yubing; Gao, Peiwei; Yang, Jianming; Shi, Feiting; Shabaz, Mohammad
Abstract : In order to study the mechanical properties and durability of cement-based composite with carbon nanotube, the test and analysis experiments are designed. Raw materials and related pharmaceutical instruments are prepared, to obtain cement-based composite with carbon nanotube samples by catalytic pyrolysis according to different proportions. The prepared sample is taken as the experimental object, and different bearing capacities are applied on different positions of the sample, to observe the change of the sample, and then, the experimental results of the mechanical properties of composite materials are obtained. The durability test results are obtained by combining the impermeability and frost resistance of the test object. The average compressive strength is 84.09 MPa, the average flexural strength is 16.9 MPa, and the crack resistance index is 22.5. In addition, the structure and diffusion coefficient of the sample also change in different degrees after the solution immersion and freeze-thaw treatment. Through longitudinal comparison, the more the carbon nanotubes are added into cement-based composite, the better its mechanical properties and durability are.